2020
DOI: 10.4102/safp.v62i1.5126
|View full text |Cite
|
Sign up to set email alerts
|

Acute stroke in the emergency department: A chart review at KwaZulu-Natal hospital

Abstract: This study was a retrospective chart review of all patients with a clinical diagnosis of stroke presenting to an ED of a regional hospital in rural KwaZulu-Natal from November 2018 to November 2019.Results: A total of 362 patient charts were screened, and 136 of the charts met the inclusion criteria for the study. Seventy per cent of the patients had pre-existing hypertension, only one patient was not on treatment and two patients were not on secondary prevention. In human immunodeficiency virus-positive patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
4
4
0
Order By: Relevance
“…This is much higher than reported previously in other provinces of South Africa (0.47 and 0.39 per annum), but similar to a recent study in the Western Cape that assessed the prevalence of atrial fibrillation in patients with ischaemic strokes and found the prevalence of ischaemic stroke to be 2%. [ 19 , 23 , 24 ] The proportion of ischaemic and haemorrhagic stroke was in keeping with local data and what is reported in the United States of America and Europe (85% and 11% respectively) but in contrast to data from other LMIC where the proportion of haemorrhagic stroke is reported as much higher ranging from 29-57%. [ 6 , 10 , 23 , 25 , 26 ] The median age of 62 years, is congruent with local stroke data, but much lower than the median age of 73 in HIC.…”
Section: Discussionsupporting
confidence: 82%
“…This is much higher than reported previously in other provinces of South Africa (0.47 and 0.39 per annum), but similar to a recent study in the Western Cape that assessed the prevalence of atrial fibrillation in patients with ischaemic strokes and found the prevalence of ischaemic stroke to be 2%. [ 19 , 23 , 24 ] The proportion of ischaemic and haemorrhagic stroke was in keeping with local data and what is reported in the United States of America and Europe (85% and 11% respectively) but in contrast to data from other LMIC where the proportion of haemorrhagic stroke is reported as much higher ranging from 29-57%. [ 6 , 10 , 23 , 25 , 26 ] The median age of 62 years, is congruent with local stroke data, but much lower than the median age of 73 in HIC.…”
Section: Discussionsupporting
confidence: 82%
“…Although the mortality rate reported in our study (22.5%) was within the range reported in other hospital-based studies of CVD in South Africa (range: 4% -33%), (6,8) it is still alarmingly high. We attribute this high mortality rate to patient-related delays in presentation for care and poorly controlled CVD risk factors in the general population.…”
Section: Discussionsupporting
confidence: 59%
“…Patient-related delays in presenting to a hospital following a CVD event can impact the effectiveness of current treatments or the eligibility of patients for these treatments. (8,15) A recent study conducted at the Our study was not without limitations. We analysed patient data collected at a single tertiary hospital, and our findings might not be generalisable to other hospitals in South Africa.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Stroke is the leading cause of morbidity, and the second leading cause of mortality in the world -responsible for 9.5% of all deaths globally (Feigin & Krishnamurthi, 2011;Lozano et al, 2012). Nearly 85% of this burden occurs in developing nations (Bham & Ross, 2005), compounded by the fact that developing countries have markedly reduced capability to support victims of stroke (Feris & Naicker, 2020). Research from South Africa shows that the local burden of stroke disease mirrors international data (Maredza et al, 2016).…”
Section: Introductionmentioning
confidence: 99%